Entrepreneurial development and innovation in family businesses and SMEs - Masouras, Andreas, 1980-; Maris, Georgios, 1979-; Kavoura, Androniki, 1972- (Advances in business strategy and competitive advantage., 2020)
"This book contributes to the understanding, improving and strengthening of entrepreneurial development, and innovation's role in family businesses and SMEs by providing both theoretical and applied knowledge in order to find how and why entrepreneurship and innovation can produce inefficient and dysfunctional outcomes"--